Factors Influencing Quiet Quitting and Employee Commitment in Casino Gaming Workplaces: Implications for Employee Retention Strategies - Paraiso, Pusha (Journal of Interdisciplinary Perspectives, 2024)
Employee turnover, particularly through "quiet quitting," presents significant challenges for the casino gaming industry, impacting operational efficiency and profitability. This study examined the factors influencing quiet quitting and employee commitment within casino gaming workplaces, providing insights into effective employee retention strategies. The researcher employs One-Way Analysis of Variance (ANOVA) and Chi-Square Test to examine and interpret data. This discussion elucidates the methodologies of these tests, focusing on their applications, assumptions, and interpretations. The findings indicate respondents exhibit low levels of quiet quitting related to psychological empowerment. However, most participants expressed that their job retention is driven by necessity, indicating a high dependence on their current employment. Additionally, the study revealed low levels of employee commitment across affective, continuance, and normative dimensions. Notably, many respondents expressed a tendency toward considering leaving their current jobs. These findings suggest that addressing quiet quitting behaviors is crucial for enhancing employee commitment and retention in the casino gaming industry.